Diagnosing chronic pancreatitis by endoscopic ultrasound assessing the association between ultrasound and pathological findings: A narrative review. Issue 1 (15th September 2022) - Yamamiya, Akira; Irisawa, Atsushi; Abe, Yoko; Arisaka, Takahiro; Ohnishi, Toshihiko; Hoshi, Koki; Suzuki, Tsunehiro; Nagashima, Kazunori; Kashima, Ken; Kunogi, Yasuhito; Sakuma, Fumi; Fukushi, Koh; et al.
Abstract: Endoscopic ultrasound (EUS) is widely recognized for its non‐invasiveness and for its usefulness in chronic pancreatitis (CP) diagnosis, including early CP. Although it is desirable to obtain a definitive diagnosis of CP by tissue sampling with EUS‐guided fine needle aspiration, histopathological changes in CP are heterogeneous in terms of the extent and the distribution of lesions. Therefore, histopathological diagnosis of appropriate tissue sampling by EUS‐fine needle aspiration is expected to be difficult. Furthermore, it is virtually impossible to match EUS images with pathological sections, making direct contrast between EUS findings and pathology difficult. This narrative review presents a discussion of the diagnosis of CP/early CP by EUS, particularly assessing the association between ultrasound and pathological findings. Recently, the histological corroboration and correlation of EUS findings related to CP have been clarified by surgical specimens, including those obtained from animal studies. Furthermore, remarkable advances have occurred in the objective and quantitative diagnosis of pancreatic fibrosis by EUS‐elastography. Future technological advances in EUS are expected to improve the accuracy of diagnosis of pancreatic fibrosis at earlier stages.